Design of Hazard Analysis Critical Control Point (HACCP) in Rendang Padang Restaurant - Erwan Adi Saputro; Moh. Nofianto; Arbiter Khalida Bramanta; A.R. Yelvia Sunarti (Nusantara Science and Technology Proceedings, 2022)
Food safety and nutrition will determine the degree of health. Many restaurants sell various types of food but not yet known whether the food served is safe or not. One of the typical foods from Padang restaurants is rendang. The cooking process of rendang needs a long time, so rendang is made in large quantities. It causes rendang to experience storage long enough that it can trigger bacterial growth. Therefore, HACCP is needed to prevent food contamination. This study aims to determine the design of HACCP in rendang padang restaurant. This research used survey and direct interview methods with the owner to determine the design and implementation of HACCP. Based on the analysis, show that the formulation of the HACCP stages shows that the main points of Critical ingredients are spices and coconut milk, receipt and preparation of raw materials, preparation of equipment used, cooking process, storage, and distribution. Corrective action that can be taken is to return raw materials and provide advice to the seller and always clean. From the results of bacterial testing on rendang, it meets the requirements of SNI 7474:2009. Padang restaurant entrepreneurs are advised to choose suppliers of raw materials implement a food safety system and apply personal hygiene and food sanitation hygiene